2022
DOI: 10.1007/s00702-022-02562-w
|View full text |Cite
|
Sign up to set email alerts
|

Motor and non-motor improvements following short-term multidisciplinary day-clinic care in Parkinson´s disease

Abstract: Background Inpatient as well as outpatient care does often not meet PD-patients’ individual needs. Introduction Day-clinic concepts encompassing a multidisciplinary team as well as therapy adjustments accompanying everyday demands aim at filling this gap. Methods This is a retrospective study on short-term effects of a 3 week multidisciplinary rehabilitation program in patients with Parkinson´s disease (PD) embedded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Published by Francis Academic Press, UK -61-ICH patients. The commonly used prognostic assessment methods in clinical practice currently include Krause, Patricia's multidisciplinary scoring system for improving clinical nursing in both motor and non motor aspects [1], and Virhammar, Johan's neurological deficit severity scoring system in the study of cerebrospinal fluid and central nervous system injury [2]. Ramspek and Chava L also conducted external validation of the prognostic evaluation model, elaborating on the relevant issues of "what, why, how, when, and where" [3].…”
Section: Related Workmentioning
confidence: 99%
“…Published by Francis Academic Press, UK -61-ICH patients. The commonly used prognostic assessment methods in clinical practice currently include Krause, Patricia's multidisciplinary scoring system for improving clinical nursing in both motor and non motor aspects [1], and Virhammar, Johan's neurological deficit severity scoring system in the study of cerebrospinal fluid and central nervous system injury [2]. Ramspek and Chava L also conducted external validation of the prognostic evaluation model, elaborating on the relevant issues of "what, why, how, when, and where" [3].…”
Section: Related Workmentioning
confidence: 99%
“…Only 7 studies; 5 in the MR group [47,50,52,53,55] and 2 in the non-MR [56,59] (Table 2) measured cognitive function, using different tests including MMSE, SCOPA-COG, MMST, MoCA, Go/no go, and D-KEFS.…”
Section: Improvement In Cognitionmentioning
confidence: 99%
“…Short-term cognitive improvement was seen in 4 studies within the MR group (Table 3); 27% in a controlled study [47], 4% in a non-controlled study [50] and only 1% in a retrospective study [52]. One retrospective study showed 1.5% worsening of cognition [53].…”
Section: Improvement In Cognitionmentioning
confidence: 99%
See 2 more Smart Citations